Designing Riverfront Settlement Banjir Kanal Timur River by Ecological Riverfront Settlement Concept - Nugraha Nugraha (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
City as a livable space should meet a good standards especially in terms of urban design and availability of facilities. Urbanization that continues to increase each year become an urge to provide housing equipped with complete infrastructure. Furthermore, high activity in urban centres causing accessibility, flood, air polution, and high noise that can affect the surrounding housing. Therefore, the availability of complete infrastructure is required along with availability of recreation and open space. In addition, Semarang as a city that have a low probability for flood will become a ideal home to live. In this case, analysis conducted aimed to perform urban design by using descriptive analysis method that is, activity analysis and space needs, site analysis, infrastructure analysis, design element analysis, aesthetics analysis. Data that need to be considered is about the type of settlement facilities and supporting relevant activities, As well as data on public perception of public space needs. The concept design plan to be implemented is